La disfuncionalidad familiar en el rendimiento escolar en el área de lengua y literatura de los estudiantes de la Escuela Fiscal Mixta no. 131 David Clemente Miranda Franco de la ciudad de Guayaquil provincia del Guayas, periodo lectivo 2010-2011 - Pilalò Vera, Edith Narcisa (2011)
Research in the Fiscal Primary School No. 131 David Clemente Franco Miranda in the city of Guayaquil in Guayas province, allows for an approach to the circumstances in which education is not only the governmental level but also because of family dysfunction environment are not only in the investigated area but also the institutions have similar characteristics in similar environments. In this paper I proposed to develop a research on the dysfunctional and school performance in the area of language and literature that raises me achievable goals ending with a description of the change strategies can be developed at school in study to It was necessary to the investigation of the variables contributing to relevant information as the scientific basis for further development work. I decided to conduct a survey to students and parents who gave me first-hand information in order to reach a conclusion and express really relevant recommendations in this paper investigated. The methods applied in this process are the inductive, deductive, historical logic and problem solving, so the qualitative and quantitative research, using appropriate instruments for its implementation It describes strategies for change that will provide a solution to the problem, action that will affect society, and particularly the school students investigated.